Music and esotericism - Wuidar, Laurence, 1978- (Aries Book Series, 2010)
This collection of essays analyzes the relationships that exist between esotericism and music from Antiquity to the 20th century, investigating ways in which magic, astrology, alchemy, divination, and cabbala interact with music. The volume seeks to dissolve artificial barriers between the history of art, music, science, and intellectual history by establishing an interdisciplinary dialogue about music as viewed against a specific cultural background. The synthesis of scientific and historical contexts with respect to music, explored here on a large scale for the first time, opens up a wealth of new approaches to music historical research, music performance, and musical composition. Each chapter presents either a unique example of music functioning within esoteric and scientific traditions or a demonstration of the influence of those traditions upon selected musical works. L'ouvrage analyse les relations entre l'ésotérisme et la musique de l'Antiquité au 20ème siècle étudiant comment la magie, l'astrologie, l'alchimie, la divination et la cabale ont interagit avec la musique. Il vise à dépasser les frontières entre l'histoire de l'art, l'histoire de la musique et l'histoire des sciences et des idées afin de nouer un dialogue interdisciplinaire sur la musique autour de contextes historiques et scientifiques précis. L'ouvrage offre une première synthèse sur les rapports entre ésotérisme et musique ainsi que diverses pistes de recherche à poursuivre.